Social Work Education that Addresses Trafficking for Sexual Exploitation: An intersectional, anti-oppressive practice framework - Gerassi, Lara; Nichols, Andrea (Anti-Trafficking Review, 2021)
Practice, policy, and research focused on trafficking for sexual exploitation and commercial sex involvement occur in the United States within a white, heteronormative social environment that must be addressed pedagogically in the classroom. Social work education increasingly includes the topic of trafficking for sexual exploitation as a stand-alone course or as sessions embedded within other courses. Yet, very little scholarship critically examines how instruction in social work on this topic can apply intersectional, anti-oppressive frameworks across micro, mezzo, and macro levels. Furthermore, current literature suggests that some social workers use exclusionary practices when addressing trafficking and commercial sex involvement, further exemplifying the need for anti-oppressive curricula. The purpose of this paper is to critically analyse how key anti-oppressive theoretical and practice frameworks should influence education on trafficking for sexual exploitation and commercial sex involvement in social work. Written by two scholars and social work instructors, we describe how we apply these frameworks to pedagogical exercises in social work courses. Finally, we argue that intersectional, anti-oppressive social work education is critical to training social work students and, ultimately, addressing the needs of people experiencing or at risk of trafficking.